Development of an Experiential Learning Model Based on Dedication to Society - Hidayah, Maulida Ulfa; Ulfah, Zakiyah; Kadir, Marniati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Optimal learning is not only seen in the presentation of the theory in the class so that students are able to know and memorize the theories. However, depending on how the student gains direct experience and then reflects on it in the process of his graduation. Also at the college level, various forms of learning through the experience process will be more acceptable, one of which is the experiential learning model. In addition, the learning process is also developed by integrating service activities into the community. To this end, the aim of this research is to design and determine the feasibility of developing a model of experiential learning based on dedication to society in the course of teaching. The method used is the Research and Development (R&D) method with the 4D (four-D) model of Thiagarajan, i.e., defining, designing, developing, and deploying. The result is that (1) the stage of model design is structured based on the results of needs analysis, as well as the preparation of the framework and product development, which are carried out with the creation of books that include the rational development of the learning model; (2) the model of experiential learning based on dedication to society is highly qualified to be used as a model of learning both from the technical side of design, material, purpose, and motivation of learning.